2018
DOI: 10.5194/adgeo-45-377-2018
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy measurement of Random Forests and Linear Regression for mass appraisal models that estimate the prices of residential apartments in Nicosia, Cyprus

Abstract: Abstract. The purpose of this article is to examine the prediction accuracy of the Random Forests, a machine learning method, when it is applied for residential mass appraisals in the city of Nicosia, Cyprus. The analysis is performed using transaction sales data from the Cyprus Department of Lands and Surveys, the Consumer Price Index of Cyprus from the Cyprus Statistical Service and the Central Bank of Cyprus' Residential Index (Price index for apartments). The Consumer Price Index and the price index for ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 8 publications
2
22
0
Order By: Relevance
“…However, when compared to simple vector machines, the Random Forests algorithm proved to more stable and robust. These findings reflect those of other authors, who argued that Random Forests could be more accurate as long as the model is designed to specify random feature subsets [17].…”
Section: Literature Reviewsupporting
confidence: 89%
“…However, when compared to simple vector machines, the Random Forests algorithm proved to more stable and robust. These findings reflect those of other authors, who argued that Random Forests could be more accurate as long as the model is designed to specify random feature subsets [17].…”
Section: Literature Reviewsupporting
confidence: 89%
“…Reviewing the literature available so far, it can be concluded that the results obtained in terms of MAPE are better than those obtained in [26] with a value of 25.2% in Nicosia or in [46] for the US with 20.9%. e results are similar to those obtained in [14] with a value that ranges from 19.02% to 15.89% in Madrid and worse than those obtained for Ljubljana in [24] with an average MAPE of 7.28.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, the conclusion emphasizes that it is not necessary to change the variables used in each county and that the accuracy of the model is practically the same using a series of common attributes for all of them. Dimopoulos et al [26] develop an application to compare the behaviour of random forest and linear regression in estimating the prices of residential apartments in Nicosia (Cyprus). e results verify that the best behaviour in predictive terms is that of random forest, with average MAPE values of 25.2%.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on timeseries analysis of multispectral Sentinel-2 datasets, Evagorou et al (2019) obtained bathymetric data for shallow waters, (up to 30 m below sea level), using freely and open distributed optical satellite images. The ratio transform algorithm was implemented for twelve (12) monthly images covering thus a whole year.…”
mentioning
confidence: 99%